2021
DOI: 10.3390/rs13142817
|View full text |Cite
|
Sign up to set email alerts
|

Satellite-Observed Multi-Scale Variability of Sea Surface Chlorophyll-a Concentration along the South Coast of the Sumatra-Java Islands

Abstract: The southern coast of Java is known as one of the most productive fishing grounds for tuna, feeding by nutrient-rich water along the coast caused by the subsurface water upwelling. This primary productivity can be evidenced by the high sea surface chlorophyll-a concentration (SSC). Based on satellite remote sensing products, we investigate the multi-scale variability in SSC along the Sumatra-Java coast. The results show that seasonal variability of SSCs is primarily due to monsoon-driven upwelling and rainfall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 59 publications
3
12
0
Order By: Relevance
“…Our results verify the role of the oceanic process related to the CIO mode in the intraseasonal variability of mixed layer Chl concentration, and underscores the differences compared to the processes of Chl responses during the MJO season (Jin et al, 2012). Xu et al (2021) reported a high Chl concentration with significant intraseasonal variability along the south coast of the Sumatra-Java Islands, which is well captured by this model (Figure 1). However, the correlation coefficient between the projected CIO mode index and intraseasonal Chl concentration averaged in the south coast of Java (10°-6°S, 105°-115°E) is only 0.23 (not significant at the 95% confidence level).…”
Section: Summary and Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results verify the role of the oceanic process related to the CIO mode in the intraseasonal variability of mixed layer Chl concentration, and underscores the differences compared to the processes of Chl responses during the MJO season (Jin et al, 2012). Xu et al (2021) reported a high Chl concentration with significant intraseasonal variability along the south coast of the Sumatra-Java Islands, which is well captured by this model (Figure 1). However, the correlation coefficient between the projected CIO mode index and intraseasonal Chl concentration averaged in the south coast of Java (10°-6°S, 105°-115°E) is only 0.23 (not significant at the 95% confidence level).…”
Section: Summary and Discussionsupporting
confidence: 83%
“…Xu et al. (2021) reported a high Chl concentration with significant intraseasonal variability along the south coast of the Sumatra‐Java Islands, which is well captured by this model (Figure 1). However, the correlation coefficient between the projected CIO mode index and intraseasonal Chl concentration averaged in the south coast of Java (10°–6°S, 105°–115°E) is only 0.23 (not significant at the 95% confidence level).…”
Section: Summary and Discussionsupporting
confidence: 62%
“…Recently, Xu et al. (2021) used daily interpolated data and outlined the intraseasonal and interannual surface Chl‐a variations in the southeastern Indian Ocean.…”
Section: Introductionmentioning
confidence: 99%
“…Satellite-based Chl-a data could be a proxy for the coastal upwelling (Siswanto et al, 2020), but because of the large missing values, most previous studies used monthly averages (e.g., Iskandar et al, 2009;Susanto & Marra, 2005). Recently, Xu et al (2021) used daily interpolated data and outlined the intraseasonal and interannual surface Chl-a variations in the southeastern Indian Ocean. The present study makes daily time series for the coastal upwelling signals based on the satellite-based Chl-a data.…”
mentioning
confidence: 99%
“…In the eastern boundary of the Arabian Sea, the southwesterly winds turn mainly into onshore equatorward winds along the southwest coast of India, generating offshore Ekman transport and coastal upwelling [10,11]. In the eastern equatorial Indian Ocean, the southeasterlies along the southern coast of Java and Sumatra islands induces upwelling off the coast [12,13]. These boundary upwelling systems are mainly characterized as offshore transport of surface water where the subsurface water upwells to the surface.…”
Section: Introductionmentioning
confidence: 99%